Peningkatan Keterampilan Membuat Mother of Sauce Melalui Model Pembelajaran Project Based Learning di SMK Putra Anda Binjai - Chairiza Azmi; Chitra Annisa Ramadhaningtyas; Lutfia Yasmin; Titis Budi Rahayu (Jurnal Pendidikan dan Sastra Inggris, 2025)
The ability to prepare mother of sauce, which serves as a foundational element in classical cooking techniques, remains a notable challenge for students at SMK Putra Anda Binjai. This subject demands a high level of precision, technical proficiency, and deep procedural understanding that is not easily achieved through conventional teaching approaches such as lectures or one-way demonstrations. This study aims to evaluate the extent to which the implementation of the Project Based Learning model can enhance students' skills in producing mother of sauce. The research employed a quasi-experimental design using a One Group Pretest-Posttest model, involving 28 eleventh-grade culinary students. Data were collected through performance-based tests and analyzed using descriptive statistics and paired sample t-tests. The results revealed an increase in the average score from 11.18 before the intervention to 17.29 after the learning process, with a significance value of 0.000, indicating a statistically meaningful improvement. The findings suggest that project-based learning not only supports the enhancement of students’ technical skills but also fosters critical thinking, collaboration, and a sense of responsibility. This research recommends the integration of project-based learning into culinary practice instruction, particularly for complex and contextual topics such as mother of sauce.